Factores pregestacionales, gestacionales y fetales asociados al parto pretérmino en pacientes atendidas en el Hospital General IESS Los Ceibos, Guayaquil, octubre 2024- mayo 2025 - Carranza Hidalgo, Salma Anahí (2025)
Preterm birth, defined as birth before the 37th week of gestation, is one of the leading causes of neonatal morbidity and mortality globally. Its etiology is multifactorial, involving a complex interaction of pregestational, gestational, and fetal conditions, which significantly influence its prevalence and associated maternal-fetal complications. The present study aimed to identify the clinical and epidemiological determinants of preterm birth in a cohort of patients treated at the General Hospital of the Ecuadorian Social Security Institute (IESS) Los Ceibos, in the city of Guayaquil, from October 2024 to May 2025. An applied, descriptive, and analytical study was designed, based on a systematic review of medical records. The sample consisted of 1,296 pregnant women belonging to the Gynecology-Obstetrics Service, which guaranteed adequate population representation. The findings revealed that 67.3% of preterm birth cases occurred in women of extreme maternal age, i.e., those under 17 or over 35 years of age. Significantly associated risk factors were also identified: gestational hypertension, urinary tract infections, a history of preterm birth, and poor prenatal care, both in frequency and quality. These results underscore the importance of implementing early detection strategies and optimizing prenatal follow-up to mitigate the incidence of preterm birth and improve perinatal and maternal outcomes, in line with evidence-based best practices.